Evaluation of Serum Cytokines Levels and the Role of Cannabidiol Treatment in Animal Model of Asthma - Vuolo, Francieli (Mediators Inflamm, 2015)
Asthma represents a public health problem and traditionally is classified as an atopic disease, where the allergen can induce clinical airway inflammation, bronchial hyperresponsiveness, and reversible obstruction of airways. Studies have demonstrated the presence of T-helper 2 lymphocytes in the lung of patients with asthma. These cells are involved in cytokine production that regulates immunoglobulin synthesis. Recognizing that T cell interaction with antigens/allergens is key to the development of inflammatory diseases, the aim of this study is to evaluate the anti-inflammatory potential of cannabidiol (CBD) in this setting. Asthma was induced in 8-week-old Wistar rats by ovalbumin (OVA). In the last 2 days of OVA challenge animals received CBD (5 mg/kg, i.p.) and were killed 24 hours after. The levels of IL-4, IL-5, IL-13, IL-6, IL-10, and TNF-α were determinate in the serum. CBD treatment was able to decrease the serum levels of all analyzed cytokines except for IL-10 levels. CBD seems to be a potential new drug to modulate inflammatory response in asthma.